Rheumatoid Cachexia Revisited: A Metabolic Co-Morbidity in Rheumatoid Arthritis - Masuko, Kayo (Frontiers in Nutrition, 2014)
Rheumatoid arthritis (RA) is a chronic inflammatory disease in which pro-inflammatory cytokines, including tumor necrosis factor (TNF)-alpha, play a crucial role. The chronic inflammation, combined with reduced physical activity, leads to muscle wasting whereas fat mass would be maintained; the resulting abnormal metabolic state is described as rheumatoid cachexia. Since the loss of muscle volume would be compensated by the increased fat mass, body mass index (BMI) is reported not to reflect the nutritional status in RA patients. The implication of rheumatoid cachexia for cardiovascular risk and clinical prognosis is not clearly understood, however, adequate control of disease activity in combination with appropriate physical exercise could be the most important strategy to control rheumatoid cachexia and related metabolic problems.